Proprotein convertase subtilisin/kexin type 9 (PCSK9) as a marker of coronary lesion severity in stable coronary artery disease (CAD) patients - Andra, Cut A.; Rambe, Aldy S.; Hasan, Refli; Sembiring, Rosita; Firman, Doni; Eyanoer, Putri C.; Mukhtar, Zulfikri; Sungkar, Taufik; Rusda, Muhammad; Amin, Mustafa M. (Narra J, 2023)
Coronary artery disease (CAD) remains a significant global health concern with considerable high morbidity and mortality and its development is influenced by various genetic and environmental factors. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a vital regulator of low-density lipoprotein receptor (LDLR) metabolism, directly impacting serum cholesterol levels. However, its role in development of CAD is not fully understood. The aim of this study was to assess the association between the level of PCSK9 and coronary lesion severity in patients with CAD. A case-control study using consecutive sampling was conducted among CAD patients at H. Adam Malik General Hospital and Murni Teguh Memorial Hospital, Medan, Indonesia. A total of 200 CAD patients were divided into two groups based on the SYNTAX score: control (score ≤22, n=100) and case (score >22, n=100). Plasma PCSK9 levels were measured from venous blood using quantitative sandwich enzyme immunoassay. The Chi-squared test was used to analyze the data. Our data suggested that PCSK9 level was associated with coronary lesion severity (p<0.001) of which high PCSK9 level was associated with severe coronary lesion. We also found that hypertension (p<0.001), smoking (p=0.072), diabetes (p<0.001), dyslipidemia (p<0.001), obesity (p=0.023), and family history (p=0.001) were associated with lesion severity. Using the receiver operating characteristic (ROC) curve analysis, the cut-off 70.35 ng/mL of PCSK9 had sensitivity 75% and specificity 78% to predict severe coronary lesion. This study highlights that PCSK9 level has moderate sensitivity and specificity to predict the coronary lesion severity among CAD patients.